COMMODIFICATION OF CHARACTERS IN THE BALI AGUNG PERFORMING ARTS “THE LEGEND OF BALINESE GODDESSES” - Suardana, Gede (E-Journal of Cultural Studies, 2017)
Bali Tourism has developed in recent decades. Its development is marked by increasing tourist arrivals, increasing tourist accommodations, attractions, and diverse tourist attractions. The development of tourism causes more and more performing arts that are commercial and profit oriented. One of the commercial performances is the art of touristic performances titled Bali Agung - The Legend of Balinese Goddesses that is a mythological story of Jayapangus marriage with Kang Cing Wei. This research uses qualitative method. The data were collected by observation techniques, interviews, and document studies. The analysis uses commodification theory. The results of this study indicate that the art of Bali Agung performances is the result of commodification seen in the production, distribution, and consumption. In the production process there are modifications to three main characters, namely Jayapangus, Kang Cing Wei, and Dewi Danu from sacred to profane. In the process of the performing there are negotiable ideas between Balinese and Western artists.